EuroSCORE II as Predictor of Mortality and Morbidity in Post-CABG Patient in Dr. Soetomo General Academic Hospital - Rianda, Rama Azalix; Semedi, Bambang Pujo; Subagjo, Agus; Avidar, Yoppie Prim (Indonesian Journal of Anesthesiology and Reanimation, 2022)
Introduction: European System for Cardiac Operative Risk Evaluation (EuroSCORE) is a scoring system to predict mortality risk after cardiac surgery. EuroSCORE II was introduced to replace and show superiority over EuroSCORE I which tends to overestimate the risk of heart surgery procedures and have a low discrimination ability. Meanwhile, this is the first study to analyze EuroSCORE II as a predictor of mortality and morbidity in Indonesians. Objective: This study aims to analyze EuroSCORE II as a predictor of mortality and morbidity in Indonesians. Methods: This is a retrospective study using medical records of CABG patients in Dr. Soetomo General Academic Hospital from January 2016 to December 2017. Results: Out of 39 Patients who have performed CABG surgery, most were male (89.7%) with the highest age range of 46-65 years (59%). Deceased patients had an average EuroSCORE II of 22.36% and SD±26.97%7%, while 27 patients who survived had an average EuroSCORE II of 6.78% and SD±6.4%. Based on morbidity assessment, EuroSCORE II only accurately predicted the risk of kidney failure and did not properly assess the length of inotropic use, vasopressors, hospitalization time, the risk of arrhythmias, low cardiac output syndrome, Durante-operative bleeding, and the need for blood transfusion. These inaccuracies occurred because the samples that were included varied based on their standard deviation and pattern-less graph. Conclusion: EuroSCORE II is inadequate to predict morbidity and mortality in postoperative patients, therefore, it is considered less effective.